TINJAUAN KETIDAKLENGKAPAN BERKAS KEMATIAN GUNA MENUNJANG KUALITAS LAPORAN DI RUMAH SAKIT BHAYANGKARA TK.II SARTIKA ASIH BANDUNG - Ayu Hendrati Rahayu; Gerinata Ginting; Riri Damayanti Apnena; Narisya Nur Intan Paba (Jurnal TEDC, 2022)
Based on observations in May 2022 carried out at Bhayangkara TK.II Sartika Asih Hospital, Bandung by taking medical record files who died in 2021, from 70 files there were 38 incomplete files and incomplete filling of death files with an average percentage of 72% which includes cause of death, time interval, and authentication. This study seeks to understand the incompleteness of the death file in order to support the quality of reports at Bhayangkara TK.II Sartika Asih Hospital, Bandung. The population in this study were medical record files who died in 2021, which were 238 medical record files. Samples were taken using the Slovin formula with the results of 70 samples. The percentage results regarding the incompleteness of the death file form at Bhayangkara TK.II Sartika Asih Hospital Bandung in 2021 based on the cause of death variable by 54%, based on the time interval variable by 87%, based on the authentication variable by 75%, and based on the overall average obtained by 72%.The author suggests that it is better to fill out the cause of death report more carefully and carefully so that the quality of reports at Bhayangkara TK.II Sartika Asih Hospital Bandung becomes more qualified.